Computer reconstruction of gene networks controlling anxiety levels in humans and laboratory mice - E. G. Vergunov; V. A. Savostyanov; A. A. Makarova; E. I. Nikolaeva; A. N. Savostyanov (Вавиловский журнал генетики и селекции, 2025)
Anxiety is a normotypic human condition, and like any other emotion has an adaptive value. But excessively high or low anxiety has negative consequences for adaptation, which primarily determines the importance of studying these two extreme conditions. At the same time, it is known that the perception of aversive stimuli associated with anxiety leads to changes in the activity of the brain’s cingulate cortex. The advantage of animals as models in studying the genetic bases of anxiety in humans is in the ability to subtly control the external conditions of formation of a certain state, the availability of brain tissues, and the ability to create and study transgenic models, including through the use of differentially expressed genes of small laboratory animals from the family Muridae with low and high anxiety. Within the framework of the translational approach, a three-domain potential gene network, which is associated with generalized anxiety in humans, was reconstructed using mouse models with different levels of anxiety by automatically analyzing the texts of scientific articles. One domain is associated with reduced anxiety in humans, the second with increased anxiety, and the third is a dispatcher who activates one of the two domains depending on the status of the organism (genetic, epigenetic, physiological). Stages of work: (I) A list of genes expressed in the cingulate cortex of the wild type CD-1 mouse line from the NCBI GEO database (experiment GSE29014). Using the tools of this database, differences in gene expression levels were revealed in groups of mice with low and high (relatively normal) anxiety. (II) Search for orthologs of DEG in humans and mice associated with anxiety in the OMA Orthology database. (III) Computer reconstruction using the ANDSystem cognitive system based on (a) human orthologous genes from stage (III), (b) human genes from the MalaCards database associated with human anxiety. The proven methods of the translational approach for the reconstruction of gene networks for behavior regulation can be used to identify molecular genetic markers of human personality traits, propensity to psychopathology.